2010
DOI: 10.1002/hipo.20886
|View full text |Cite
|
Sign up to set email alerts
|

Right‐hemispheric dominance of spatial memory in split‐brain mice

Abstract: Left-right asymmetry of human brain function has been known for a century, although much of molecular and cellular basis of brain laterality remains to be elusive. Recent studies suggest that hippocampal CA3-CA1 excitatory synapses are asymmetrically arranged, however, the functional implication of the asymmetrical circuitry has not been studied at the behavioral level. In order to address the left-right asymmetry of hippocampal function in behaving mice, we analyzed the performance of "split-brain" mice in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 15 publications
(17 reference statements)
10
49
2
Order By: Relevance
“…These results support findings that both hippocampal hemispheres contribute to spatial learning [30]. MWM Fixed Platform acquisition deficits [5,11] have been shown in right hemisphere injury, though contrary to the present findings, others have noted acquisition deficits also from left lateral injuries [9,10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results support findings that both hippocampal hemispheres contribute to spatial learning [30]. MWM Fixed Platform acquisition deficits [5,11] have been shown in right hemisphere injury, though contrary to the present findings, others have noted acquisition deficits also from left lateral injuries [9,10].…”
Section: Discussionsupporting
confidence: 84%
“…The left and right lateral injury deficits seen in the Fixed Platform probe trial are consistent with existing left [27] and right [30] lateral injury reference memory expression deficits. These results support findings that both hippocampal hemispheres contribute to spatial learning [30].…”
Section: Discussionsupporting
confidence: 81%
“…We also found that high-frequency stimulationinduced LTP is only expressed at CA3-CA1 synapses when presynaptic input originates in the left CA3. Unilateral hippocampal lesions in mice have not revealed a distinct hemispheric contribution to long-term memory (25), although split-brain mice with left eye deprivation showed greater spatial memory accuracy than those with right eye deprivation when the environmental complexity increased (26). Studies in rats have either shown no effect of unilateral lesions (27,28) or no asymmetry of hippocampal function (27,29), or have produced inconsistent findings (30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…Also in roll it was also increased more in the right fore limb in the diagonal back right direction, whereas the left limb did not respond similarly (Figure 2). Spatial processing is primarily in the right hemisphere (Shinohara et al, 2012). Stepping movements are presumed to represent subcortical startle reactions, as opposed to a reaction mediated by the cerebral cortex, which approximately halves the reaction time from 150 to 80 ms (Valls-Solé et al, 1999).…”
Section: Discussionmentioning
confidence: 99%